2016
DOI: 10.1080/08927936.2015.1069988
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Cross-over Exploratory Study of the Effect of Visiting Therapy Dogs on College Student Stress Before Final Exams

Abstract: This exploratory study investigated the effect of visiting therapy dogs on college-student perceived and physiological stress the week prior to final exams. Students (n = 78) were randomly assigned to order of a therapydog intervention and attention-control condition, each 15 minutes long. Students completed the Perceived Stress Scale (PSS), a stress visual analog scale (SVAS), and provided saliva for measuring nerve growth factor (sNGF) and alpha amylase (sAA), prior to randomization. Saliva samples and SVAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 50 publications
(65 reference statements)
7
84
0
Order By: Relevance
“…These results are broadly consistent with previous studies that have reported improvements in anxiety, mood, well-being, and perceived stress in college students after a therapy dog intervention [6,17,18,20,21]. Indeed, across our three measures, interacting with the dog appeared to be essential to the positive pre–post shift experienced by the students, with the presence of the handler having either a neutral (well-being and anxiety), or even a detrimental (mood) effect on outcome measures.…”
Section: Discussionsupporting
confidence: 92%
“…These results are broadly consistent with previous studies that have reported improvements in anxiety, mood, well-being, and perceived stress in college students after a therapy dog intervention [6,17,18,20,21]. Indeed, across our three measures, interacting with the dog appeared to be essential to the positive pre–post shift experienced by the students, with the presence of the handler having either a neutral (well-being and anxiety), or even a detrimental (mood) effect on outcome measures.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with other studies (Barker et al, 2005; although Barker used a different biomarker (cortisol) so it is not certain that they are measuring the same thing. A more recent study did not find any change in biomarkers, although it did in perceived stress (Barker et al, 2016). This study used different measures (STAI and blood pressure instead of the perceived stress scale and cortisol), however, the student populations were similar, stressed students with more females participating.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study did find that students who attended animal-assisted therapy for an eight week course reported less homesickness and increased satisfaction and the dogs created a relaxing, soothing environment, however no measure of stress was reported (Binfet & Passmore, 2016). A randomised control trial with students stressed by an examination period reported significant decreases in perceived stress after 15 min with a dog, although there were no changes in salivary cortisol levels (Barker et al, 2016). Similarly, studies have found university students report lower levels of anxiety and loneliness following engagement with a therapy dog, along with improvements in the perception and accessibility of counselling services (Daltry & Mehr, 2015;Stewart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nepps et al [20] found a significant reduction in state anxiety as measured by the STAI in patients in a mental health inpatient unit following a one-hour group session with a therapy dog, and Hoffmann et al [48] found a significant reduction in state anxiety in patients hospitalized with major depression following a 30-minute intervention in the presence of a dog compared to a control group. A study by Barker et al [50] examining the effects of a therapy dog on college student stress prior to final exams found that perceived stress as measured on a stress visual analog scale was significantly reduced following the therapy dog intervention compared to the control condition.…”
Section: Discussionmentioning
confidence: 99%